Termite activity and decomposition are influenced by digging mammal reintroductions along an aridity gradient. (October 2016) - Coggan, Nicole V.; Hayward, Matthew W.; Gibb, Heloise
Abstract: Species declines can have broader impacts on ecosystems, particularly when those species act as ecosystem engineers. Ecosystem engineers modify habitats, indirectly shaping biotic communities. Environmental attributes may limit the direct influence of engineers on habitat properties, indirectly affecting other species and ecological functioning. We used three sites differing in abiotic properties, where endangered digging mammals had been reintroduced, and hypothesised that: Reintroduced mammals affect resource consumption and abandonment by termites, and local factors influence termite interactions with reintroduced mammals. We therefore performed two manipulative experiments: first testing the effects of depth on termite consumption of resources, second, testing resource abandonment by termites following simulated disturbances by determining the proportion of termites remaining at disturbed resources relative to undisturbed controls. Experiments were conducted inside reintroduction enclosures and compared against controls. Resource consumption was ∼25% lower, and resource abandonment ∼50% higher where digging mammals were reintroduced and termite responses were consistent with decreasing aridity. The near-extinction of native digging mammals from much of Australia is likely to have significantly altered termite activity and decomposition, but impacts may be context-dependent, with aridity potentially playing a key role. Our work suggests, counterintuitively, that ecosystem impacts of reintroductions may be lower in resource-poor sites. Graphical abstract: Highlights: Termite response to digging mammal reintroduction compared along ecological gradients. Resource consumption 25% lower, resource abandonment 50% higher in reintroduction enclosures. Context-dependent responses to reintroductions were consistent with decreasing aridity. Ecosystem impacts of reintroductions were weaker in resource-poor sites.